Diffracting Digital Images in the Making. (2nd January 2021) - Dawson, Ian; Back Danielsson, Ing-Marie; Jones, Andrew Meirion; Minkin, Louisa; Reilly, Paul
Abstract : This paper presents a diffractive dialogue between ethnographic accounts of imagery, digital or computational imaging, and art and archaeology practices. It develops the notion of images in the making in the context of the digital domain, to discuss what an image is and can be today. It focuses on two digital imaging techniques developed within archaeology and cultural heritage – reflectance transformation imaging and structure from motion photogrammetry – exploring how these techniques play out in heritage and art world contexts and practices. The paper highlights digital images as unstable compositions, and explores how digital images in the making enable us to reconsider the shifting temporal character of the image, and discuss the way in which the digital image forces us to disrupt the representational assumptions bound up in the relationship between the virtual and the actual. The authors argue that the diffractive moments in these encounters between archaeology and art practice disclose the potential of digital imaging to recursively question the complex ontological composition of images and the ability of images to act and affect.